Patient experience with non-invasive prenatal testing (NIPT) as a primary screen for aneuploidy in the Netherlands - Syanni A. Kristalijn; Karen White; Deanna Eerbeek; Emilia Kostenko; Francesca Romana Grati; Caterina M. Bilardo (BMC, 2022)
Abstract Background Non-invasive prenatal testing (NIPT) as a screening method for trisomy 21 and other chromosomal abnormalities has been adopted widely across the globe. However, while many clinical validation studies have been performed, less is known regarding the patient experience with NIPT. This study explored how individuals experience NIPT in a pre- and post-test setting, where NIPT is broadly available as a primary screening method with the option of reporting beyond common trisomies. Methods Participants were recruited using social media with a strategy designed to select individuals who had the option to have NIPT as part of the TRIDENT-2 study (In the Netherlands, NIPT is only available within the TRIDENT studies executed by the NIPT consortium. This research was done independently from the NIPT consortium.) in the Netherlands. The study used online questionnaires and semi-structured interviews. Both were developed around a patient experience framework consisting of seven themes: information, patient as active participant, responsiveness of services, lived experience, continuity of care and relationships, communication, and support. Results Overall, 4539 questionnaire responses were analyzed and 60% of the respondents had experienced NIPT. Of those, 1.7% received a high-risk result for trisomy or another chromosomal copy number variant (referred to as an "additional finding"). Overall, participants felt they had received sufficient information and had control over their decision regarding whether or not to choose NIPT. The vast majority of respondents who had NIPT were positive about their experience and would use it again. Those with results showing an increased probability for trisomy or additional findings were more likely to report negative feelings such as tension and anxiety, and less likely to feel that they had been sufficiently prepared for the implications of their results. Conclusions The patient experience with first-tier NIPT in the Netherlands was largely positive. Areas for improvement included counseling on the implications of screening and the different possible outcomes of NIPT, including additional findings that may be uncovered by expanding NIPT beyond the common trisomies. The experiences reported in this study may be useful for other countries intending to implement NIPT.